Pendidikan dan Pelatihan Menghubungkan Teori dan Praktik Mahasiswa sebagai Guest Experiment Business Luxury Hotel di Jakarta - Ida Ayu Nyoman Yuni Devi Antari; Cok Istri Tenisia Iswari Dewi; Ni Made Maya Arya Yulisa (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
The main purpose of a Business Luxury Hotel is to provide a comfortable and safe place to stay for guests who are travelling on business or leisure. Business travellers, executives and professionals often require exclusive, luxurious accommodation equipped with high-quality facilities and services for business meetings, conferences and corporate events. This activity uses a qualitative method of descriptive analysis. This activity aims to connect the theory and practice of Business Luxury Hotel services. From this activity has the results of Business Luxury Hotel Services in Jakarta need to be improved, especially in guest experience activities and guest activities need to be given extra services in accordance with the standards set by the world hotel business.